The Life Skills of Older Americans: Association with Economic, Psychological, Social, and Health Outcomes - Steptoe, Andrew (Sci Rep, 2018)
Studies of children and adolescents indicate that success in life is determined in part by attributes such as conscientiousness, emotional stability and sense of control, independently of childhood socioeconomic status and cognitive ability. Less is known about the role of these characteristics at older ages. This study investigated the relationship of five life skills – conscientiousness, emotional stability, persistence, optimism and sense of control – with a range of outcomes in 8,843 participants (mean age 72.57 years) in the Health and Retirement Study, a representative study of older Americans. More life skills were associated with greater wealth and income, better emotional wellbeing, stronger social relationships, less loneliness, better health, fewer chronic illnesses and impaired activities of daily living, better mobility and less obesity, after controlling for childhood socioeconomic status and current cognitive ability. Longitudinally, more life skills predicted emotional wellbeing, less loneliness and more prosocial behavior, better health and mobility over a 4 year period. Associations were independent of gender, ethnicity, family background, education and cognitive ability. The number of attributes was important rather than any single life skill. Life skills continue to matter at advanced ages, and fostering these characteristics in older adults may pay dividends in terms of later life health and wellbeing.